1994
DOI: 10.1007/bf00283421
|View full text |Cite
|
Sign up to set email alerts
|

α-Domain of human metallothionein IA can bind to metals in transgenic tobacco plants

Abstract: With a view to exploring its use as a metal-binding factor in transgenic plants we prepared the alpha-domain of metallothionein by reconstitution of rabbit apometallothionein and proteolysis of MT-1 and MT-2 with subtilisin. The isolated alpha-domains were characterised by UV and CD spectroscopy Double-Stranded. DNA encoding the alpha-domain (106 bp) of the human MT-IA was constructed from chemically synthesized oligomers by repair synthesis and enzymatic ligation, cloned into pUC19 and sequenced. A expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Studies on this field are increasing and its mechanism is more and more clear [33][34][35][36][37][38][39][40][41]. Using transgenic technology is a tendency in the future to create an ideal species purposely.…”
Section: Perspectivementioning
confidence: 99%
“…Studies on this field are increasing and its mechanism is more and more clear [33][34][35][36][37][38][39][40][41]. Using transgenic technology is a tendency in the future to create an ideal species purposely.…”
Section: Perspectivementioning
confidence: 99%
“…Various MT genes Ð mouse MTI, human MTIA (alpha domain), human MTII, Chinese hamster MTII, yeast CUP1, pea PsMTA Ð have been transferred to Nicotiana sp., Brassica sp. or A. thaliana (Lefebvre et al, 1987;Maiti et al, 1988Maiti et al, , 1989Maiti et al, , 1991Misra and Gedamu, 1989;Evans et al, 1992;Yeargan et al, 1992;Brandle et al, 1993;Pan et al, 1993Pan et al, , 1994aElmayan and Tepfer, 1994;Hattori et al, 1994;Hasegawa et al, 1997). As a result, varying degrees of constitutively enhanced Cd tolerance have been achieved, being maximally 20-fold compared with the control.…”
Section: Mts and CD Tolerancementioning
confidence: 99%
“…The pZSS5 protein belongs to a family of cysteine proteinases from a wide range of plant and animal species [35,36]. pZSS6 cDNA encodes a metallothionein-like protein which belongs to a family of heavy-metal-binding proteins functioning coordinately as a detoxifying mechanism [39,49]. The nucleotide sequence analysis of pZSS7 cDNA shows that we have isolated the same MPI proteinase inhibitor gene as Cordero et aL [ 12].…”
Section: ~G a A T~c A A A T C G T G T T T A G G T G A G A C C C A A~amentioning
confidence: 99%
“…James et al [26] showed that starvationinduced protein degradation was correlated with an overall increase of proteolytic activities; furthermore, the use of inhibitors specific for cysteine proteinases clearly demonstrated that cysteine proteinases participate in protein degradation processes during sugar starvation [26]. The protein breakdown may release metal ions which have to be either stored and/or transported for further processes or sequestered to prevent their toxic effects [9,39,49]. Metallothionein-like proteins are thought to be involved in this detoxification role as recently proposed by BuchananWollaston [9] who isolated a cDNA clone for a senescence-specific metallothionein-like gene from Brassica napus.…”
Section: ~G a A T~c A A A T C G T G T T T A G G T G A G A C C C A A~amentioning
confidence: 99%